Final answer:
To match the logical expressions with their logically equivalent negations, we apply De Morgan's laws and understand quantifiers. The matches are a) - i), reflecting the negation of a universal and conjunctive statement as an existential and disjunctive one, and b) - ii), where the negation of an existential and disjunctive statement is universal and conjunctive. The negations of c) and d) refer back to the original statements a) and b), respectively.
Step-by-step explanation:
Matching the given logical expressions with statements that are logically equivalent to their negations involves understanding the rules of logic, particularly De Morgan's laws and the nature of quantifiers. The universal quantifier (∀) indicates that a statement applies to all elements, while the existential quantifier (∃) indicates that there exists at least one element for which the statement is true.
Starting with a) ∀x(P(x) ∧ Q(x)), the negation would be 'There is not an element x such that both P(x) and Q(x) are true.' Applying De Morgan's laws, we get the equivalent statement 'There exists an element x such that P(x) is not true or Q(x) is not true,' which corresponds to i) ∃x(¬P(x) ∨ ¬Q(x)).
Next, for b) ∃x(P(x) ∨ Q(x)), the negation reads 'There is no element x such that P(x) or Q(x) is true.' This can be rewritten as 'For all elements x, neither P(x) nor Q(x) is true,' translating to ii) ∀x(¬P(x) ∧ ¬Q(x)).
We can now easily deduce that the negation of c) ¬∀x(P(x) ∧ Q(x)) is actually the original statement a) ∀x(P(x) ∧ Q(x)) since double negation cancels out, and d) ¬∃x(P(x) ∨ Q(x)) would translate back to b) ∃x(P(x) ∨ Q(x)) again due to double negation.
Therefore, the original matching is a) - i), b) - ii), c) - a), and d) - b).